Form og formidling knytt til nynorsken - Helset, Stig Jarle; Brunstad, Endre (Skriftserien, 2022)
The starting point for this issue of Skriftkultur is the 150th anniversary of Ivar Aasen's launch of a national language, which at the time lacked freedom of choice in form and conjugation, but has since developed, for specific historical reasons, into today's Nynorsk, characterized by great freedom of choice compared to the vast majority of other official written languages in the world. Constant changes to the language's orthography throughout the 20th century led to both resistance to and difficulties in implementing the reforms. Publishers and newspapers created their own house rules, and a number of studies have shown that students at all levels and even teachers have had difficulty keeping track of what is correct in Nynorsk at any given time. Likewise, students probably have greater exposure to Bokmål than Nynorsk, even in the core area for Nynorsk in Western Norway, which can create challenges for Nynorsk users. In the six scholarly articles, the authors discuss the challenges and opportunities linked to the use of, exposure to and instruction in written Nynorsk. The articles include questions related to the use of house styles in Nynorsk organisations, deviations from standard Nynorsk orthography in student texts, and exposure to and instruction in Nynorsk in educational settings. In a broader perspective, the question of Nynorsk's continuing evolution also concerns the place and functions the language fills, that is to say, the kinds of social practices that are at the foundation of Nynorsk. This publication will be relevant for students, researchers and others who are interested in written Nynorsk practices.